Ømålsordbogen og mejetærskergenerationen - Gudiksen, Asgerd (Nordiske Studier i Leksikografi, 2006)
Ømålsordbogen and the Combine Harvester Generation. The topic of this paper is the description of neologisms in a Danish dialect dictionary, Ømålsordbogen (The Dictionary of the Insular Dialects). Ømålsordbogen covers the period from 1750-1945 with 1850-1920 as its core period. The description of the neologisms in the dictionary, especially those reflecting agricultural developments in the late 19th and early 20th century, has become more thorough than originally planned regarding both definitions, encyclopaedic information and selection of entries. This growing interest in the later part of the period covered by the dictionary could be explained by the fact that this period has now become historical whereas in the 1920’s, when the project began, these newer phenomena were contemporary to the editors and considered to be of less interest – or simply left unnoticed.